A Comprehensive Data and Project Management Platform: A Case Study of a Central Bank - Sardar, Souryajyoti; Bandyopadhyay, Pulastya; Sanyal, Anirban (Journal of information & knowledge management, 2016)
This study considers an efficient way to manage different aspects of a Central Bank’s Data Warehousing project using a custom built data and project management platform. Although the key aspect of managing a Data Warehouse is of course data management, but simultaneously the management of on-going projects related to data integration, website, internal and external human resources, etc. are also important. Data Warehousing in Central Banks is strategically different with other Commercial Bank/Corporate Data Warehousing project in terms of functionality/purpose. A typical Data Warehouse of a Commercial Bank or Corporate body primarily consists of the data generated out of their business operations. On the other hand, a Central Bank collects data from such Commercial Banks, Corporate bodies or Regulatory bodies for regulatory or supervisory purpose along with data on various subject domains allied to central banking compiled within the organisation. As a result, management of such diverse data sources is a major challenge for every central bank. Further, the traditional project management concepts are not applicable as-it-is in the context of a Central Bank. Keeping in view these particularities, and the shortcomings of available commercial project management tools, a comprehensive Information Management System has been built in Reserve Bank of India. The development was done in-house and based on open source platform. The salient features of this system are: (1) An all-in-one monitoring platform to monitor different aspects of Data Warehousing and Data Management project through a single window. (2) Scalability. (3) Cross-platform usability. This study presents the background, design and development of the system in detail.